1987
DOI: 10.23986/afsci.72275
|View full text |Cite
|
Sign up to set email alerts
|

The nitrate concentration of domestic vegetables on Helsinki market in summer and autumn 1984

Abstract: Abstract. Nitrate concentration of some domestic vegetables at Helsinki district market was studied during the summer and autumn months of the year 1984. The species were cabbage (Brassica oleracea var capitata), Chinese cabbage ( Brassica pekinensis) , kohlrabi (Brassica oleracea var gongylodes), turnip ( Brassica rapa), carrot (Daucus Carola subsp. salivas) and crisphead and butter head lettuce (Lactuca saliva var. capitata). The 395 samples were analysed with an ion specific electrode.There was a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The large differences reflect the wide variety of products analyzed. They are consistent with the levels expected from the nitrate contents of the vegetables used as ingredients (Siciliano et al, 1975;Garcia-Rocht & Ilnitski, 1986;Ahonen et al, 1987). The highest levels of nitrate were found in those soups containing spinach, which in common with celery, red-beet, and Swiss chard, can store relatively large quantities of nitrate.…”
Section: Resultssupporting
confidence: 83%
“…The large differences reflect the wide variety of products analyzed. They are consistent with the levels expected from the nitrate contents of the vegetables used as ingredients (Siciliano et al, 1975;Garcia-Rocht & Ilnitski, 1986;Ahonen et al, 1987). The highest levels of nitrate were found in those soups containing spinach, which in common with celery, red-beet, and Swiss chard, can store relatively large quantities of nitrate.…”
Section: Resultssupporting
confidence: 83%
“…Conversely, Nilsson (1979) found higher nitrate levels in organic cabbages than in those fertilized with soluble NPK, whereas Ahonen et al (1987) and Stopes et al (1988) did not obtain significant differences between conventional and organic cabbages.…”
Section: Food Stores Farmmentioning
confidence: 70%
“…Data source Organic Conventional Conventional Siciliano et al (1975) 784 0.5 Nilsson (1979) 171 84 Causeret (1984) 159.5 (2.5 -791.3)* 1.1 (0.1 -10.1) Garcı´a-Roche´and Ilnitsky (1986) 407.9 (143.5 -932.9) 0.6 (0.0 -2.4) Ahonen et al (1987) 393.8 422.0 Schuster and Lee (1987) 671.6 Non-detected Lakhidov et al (1994) 666.7 -918.74 Wieczorek and Traczyk (1995) 177.2 Non-detected Rutkowska (1997) 728.4 Santamaria et al (1999) 400 (8 -929) Souci et al (1999) 1070.0 (10.0 -3230.0) Amr and Hadidi (2001) 34.0 (1.3 -53.7) 1.0 (Non-detected -2.6) Elmadfa (2001) 740 1070 Yordanov et al (2001) 196.9 1.02 Ximenes et al (2000) 1829.0 Zhong et al (2002) 1530 Tamme et al (2006) 437 (74 -1138) Non-detected Susin et al (2006) 881 (112 -1864) 0.2 (Non-detected -0.4) Note: *Mean (range). Table 6.…”
Section: Nitrate Nitritementioning
confidence: 99%
“…Nitrate contents in cabbage ranging from 117 -1 680 mg NaNO 3 /kg FW (mean 911 mg) were somewhat higher than those in other countries [2,8,16,17], although Meah et al [4] found that, due to seasonal variations, the nitrate contents in cabbage ranged from 40 -2 800 mg NaNO 3 /kg FW with mean values from 150 mg NaNO 3 /kg FW in March to 1600 mg NaNO 3 /kg FW in July.…”
Section: Nitrite Levels In Potatoes and Cabbagementioning
confidence: 80%